Sosialisasi Ragam Hias Arsitektur Melayu Desa Rantau Bais Sebagai Wisata Budaya - Repi Repi; Yose Rizal; Indah Muzdalifah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Socialization of the decorative variety of Malay architectural buildings in Rantau Village can be useful to introduce cultural heritage in the form of Malay architectural buildings that have unique shapes. The implementation of the socialization introduces and provides understanding to the Rantau Bais village community about the cultural potential that can be developed into a cultural tourism destination. The socialization was carried out by presenting village officials, community leaders, tribal leaders and Tourism Awareness groups in one meeting and in the field. To determine the participants' understanding, pretest and posttest were conducted. From the results of the socialization from the beginning, many participants did not know about the potential and uniqueness of Malay architects in house buildings.